Pyrene, a Test Case for Deep-Ultraviolet Molecular Photophysics - Picchiotti, Alessandra; Nenov, Artur; Giussani, Angelo; Prokhorenko, Valentyn I; Miller, R J Dwayne; Mukamel, Shaul; Garavelli, Marco (The journal of physical chemistry letters, 2019)
We determined the complete relaxation dynamics of pyrene in ethanol from the second bright state, employing experimental and theoretical broadband heterodyne detected transient grating and two-dimensional photon echo (2DPE) spectroscopy, using pulses with duration of 6 fs and covering a spectral range spanning from 250 to 300 nm. Multiple lifetimes are assigned to conical intersections through a cascade of electronic states, eventually leading to a rapid population of the lowest long-living excited state and subsequent slow vibrational cooling. The lineshapes in the 2DPE spectra indicate that the efficiency of the population transfer depends on the kinetic energy deposited into modes required to reach a sloped conical intersection, which mediates the decay to the lowest electronic state. The presented experimental-theoretical protocol paves the way for studies on deep-ultraviolet-absorbing biochromophores ubiquitous in genomic and proteic systems.